Electrode materials, electrodes and all-solid-state batteries
By interposing a fluoride solid electrolyte layer between the active material and sulfide solid electrolyte in all-solid-state batteries, the resistance increase during durability is minimized, improving the battery's conductivity and durability.
Patent Information
- Application Number
- JP2022119623
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-07-27
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-07-27
AI Technical Summary
Sulfide solid electrolytes in all-solid-state batteries face accelerated deterioration due to direct contact with active materials, leading to increased ionic conductivity loss over time.
Incorporating a fluoride solid electrolyte as a first layer between the active material and sulfide solid electrolyte, with a sulfide solid electrolyte as a second layer, to reduce direct contact and minimize resistance increase during durability.
The proposed electrode structure with fluoride and sulfide solid electrolytes significantly reduces the rate of resistance increase, enhancing the durability and conductivity of all-solid-state batteries.
Smart Images

Figure 0007605795000003 
Figure 0007605795000004 
Figure 0007605795000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrode material, an electrode, and an all-solid-state battery. [Background technology]
[0002] JP 2014-154407 A (Patent Document 1) discloses a composite active material including composite particles containing an oxide solid electrolyte that coats an active material, and a sulfide solid electrolyte that coats the composite particles. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-154407 A Summary of the Invention [Problem to be solved by the invention]
[0004] Hereinafter, solid electrolyte may be abbreviated as "SE." For example, sulfide solid electrolyte may be abbreviated as "sulfide SE."
[0005] Sulfide SE has both high ionic conductivity and excellent moldability. Sulfide SE is suitable for bulk-type all-solid-state batteries. However, direct contact of sulfide SE with active materials in electrodes can accelerate degradation of sulfide SE. Degradation of sulfide SE can result in, for example, loss of ionic conductivity.
[0006] In order to reduce direct contact between the sulfide SE and the active material, it has been proposed to form composite particles by coating the active material with an oxide SE. In addition, it has also been proposed to coat the composite particles with a sulfide SE to promote the formation of an interface between the composite particles and the sulfide SE. The combination of the active material, oxide SE, and sulfide SE is expected to reduce the initial resistance. However, there is room for improvement in the rate of increase in resistance after durability testing.
[0007] An object of the present disclosure is to reduce the rate of increase in resistance after durability testing. [Means for solving the problem]
[0008] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.
[0009] 1. The electrode material includes a composite particle. The composite particle includes a core particle and a coating layer. The coating layer coats at least a portion of the surface of the core particle. The core particle includes an active material. The coating layer includes a first layer and a second layer. At least a portion of the first layer is disposed between the core particle and the second layer. The first layer includes a first solid electrolyte. The second layer includes a second solid electrolyte. The first solid electrolyte is a fluoride. The second solid electrolyte is a sulfide.
[0010] Conventionally, an oxide SE is interposed between an active material and a sulfide SE. The oxide SE (e.g., LiNbO3, etc.) tends to increase reaction resistance during durability.
[0011] In the electrode material of "1" above, a fluoride SE (first SE) is interposed between an active material (core particle) and a sulfide SE (second SE). According to the new findings of the present disclosure, the reaction resistance of the fluoride SE tends to be less likely to increase than that of the oxide SE. During durability testing, the reaction resistance of the fluoride SE is less likely to increase, and this is expected to reduce the rate of increase in resistance.
[0012] 2. In the electrode material according to the above item "1," the second layer may further include a first solid electrolyte in addition to the second solid electrolyte. In the second layer, the volume fraction of the second solid electrolyte is larger than the volume fraction of the first solid electrolyte.
[0013] When the first layer is formed, a portion of the first SE (fluoride SE) may not adhere to the core particle. Also, when the second layer is formed, the first SE that was adhered to the core particle may fall off. As a result, fragments of the first SE may be generated. If fragments of the first SE that are not incorporated into the composite particles and exist independently diffuse into the electrode material, electronic and ionic conduction in the electrode may be inhibited. It is expected that the electronic and ionic conduction in the electrode will be promoted by the fragments of the first SE not diffusing into the electrode material but being incorporated into the second layer.
[0014] 3. In the electrode material according to the above item "1" or "2," the second layer may further contain an active material in addition to the second solid electrolyte. In the second layer, the volume fraction of the second solid electrolyte is larger than the volume fraction of the active material.
[0015] During the formation of the first layer, a part of the core particle (active material) may be lost. This may result in the generation of active material chips. The chips generated by the loss of the core particle may also be referred to as "chipping". The active material chips may also be generated during the formation of the second layer. If the active material chips diffuse into the electrode material, the electronic and ionic conduction in the electrode may be inhibited. It is expected that the electronic and ionic conduction in the electrode will be promoted by the active material chips not diffusing into the electrode material and being incorporated into the second layer.
[0016] 4. In the electrode material according to the above item "1," the second layer may further include a first solid electrolyte and an active material in addition to the second solid electrolyte. In the second layer, the volume fraction of the second solid electrolyte is larger than the total volume fraction of the first solid electrolyte and the active material.
[0017] The second layer may incorporate both strips of the first SE and strips of active material.
[0018] 5. In the second layer described in "4" above, the first solid electrolyte may be attached to the active material.
[0019] For example, when forming the second layer, if core particles are missing, composite flakes containing the active material and the first SE may be generated.
[0020] 6. In the electrode material according to any one of the above "1" to "5", the first solid electrolyte may be, for example, 1 to 10 parts by mass with respect to 100 parts by mass of the active material. The second solid electrolyte may be, for example, 0.1 to 20 parts by mass with respect to 100 parts by mass of the active material.
[0021] 7. In the electrode material according to any one of the above "1" to "6", the first solid electrolyte may be represented by the following formula (1). Li 6-nx M x F6…(1) In the above formula (1), x satisfies 0 < x < 2. M is at least one selected from the group consisting of a semi-metal atom and a metal atom other than Li. n indicates the oxidation number of M.
[0022] The fluoride SE represented by the above formula (1) tends to have a low tendency to increase the reaction resistance during durability.
[0023] 8. In the electrode material according to the above "7", in the above formula (1), M may include, for example, an atom having an oxidation number of +4.
[0024] 9. In the electrode material according to the above "7" or "8", in the above formula (1), M may include, for example, an atom having an oxidation number of +3.
[0025] 10. In the electrode material according to any one of the above "7" to "9", in the above formula (1), M may include, for example, at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr.
[0026] 11. The electrode includes the electrode material according to any one of the above "1" to "10".
[0027] 12. The all-solid-state battery includes the electrode according to the above "11".
[0028] All-solid-state batteries are expected to have a low rate of resistance increase during durability.
[0029] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the present embodiment do not limit the technical scope of the present disclosure. The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are non-restrictive. The technical scope of the present disclosure encompasses all modifications within the meaning and scope equivalent to the description of the claims. For example, it is originally intended that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Brief description of the drawings]
[0030] [Figure 1] FIG. 1 is a first conceptual diagram showing an example of a composite particle in this embodiment. [Diagram 2] FIG. 2 is a second conceptual diagram showing an example of a composite particle in this embodiment. [Diagram 3] FIG. 3 shows an example of a cross-sectional SEM image of a composite particle and an element mapping image obtained by SEM-EDX. [Figure 4] FIG. 4 is a schematic flow chart of the method for producing composite particles in this embodiment. [Diagram 5] FIG. 5 is a conceptual diagram of the all-solid-state battery in this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] <Terms and definitions> The words "comprise," "include," "have," and variations thereof (e.g., "consisting of") are open-ended. The open-ended form may or may not include additional elements in addition to the required elements. The words "consisting of" are closed-ended. However, the closed form does not exclude additional elements that are normally associated with the technology or that are unrelated to the technology disclosed. The words "consisting essentially of" are semi-closed. The semi-closed form allows for the addition of elements that do not substantially affect the basic and novel characteristics of the technology disclosed.
[0032] Expressions such as "may" and "may" are used in the permissive sense, meaning "to have the possibility," rather than in the obligatory sense, meaning "to have to."
[0033] Elements expressed in the singular form include the plural form unless otherwise specified. For example, a "particle" can mean not only "one particle" but also "an aggregate of particles (powder, powder, particle group)."
[0034] For example, a numerical range such as "m to n%" includes an upper limit and a lower limit. That is, "m to n%" indicates a numerical range of "m% or more and n% or less." Furthermore, "m% or more and n% or less" includes "more than m% and less than n%." Furthermore, a numerical value arbitrarily selected from within the numerical range may be set as a new upper limit or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, in a figure, or the like.
[0035] All numerical values are modified by the term "about." The term "about" may mean, for example, ±5%, ±3%, ±1%, etc. All numerical values may be approximations that may vary depending on the application of the disclosed technology. All numerical values may be expressed with significant figures. Measurements may be average values of multiple measurements. The number of measurements may be three or more, five or more, or ten or more. In general, the more measurements are taken, the more reliable the average value is expected to be. Measurements may be rounded off based on the number of significant figures. Measurements may include errors associated with, for example, the detection limits of the measuring device.
[0036] When a compound is expressed by a stoichiometric composition formula (e.g., "LiCoO2", etc.), the stoichiometric composition formula is merely a representative example of the compound. The compound may have a non-stoichiometric composition. For example, when lithium cobalt oxide is expressed as "LiCoO2", unless otherwise specified, the lithium cobalt oxide is not limited to the composition ratio of "Li / Co / O=1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. Furthermore, doping, substitution, etc. with trace elements may also be allowed.
[0037] "Semi-metals" include B, Si, Ge, As, Sb, and Te. "Metals" refers to elements from Groups 1 to 16 of the periodic table, other than "H, B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se." When an inorganic compound contains at least one of a semi-metal and a metal and F, the semi-metal and the metal may have a positive (+) oxidation number.
[0038] The term "electrode" is a general term for positive and negative electrodes. The electrode may be a positive electrode or a negative electrode.
[0039] The "thickness" of the coating layer, the first layer, and the second layer can be measured by the following procedure. A sample is prepared by embedding the composite particles in a resin material. The sample is subjected to a cross-section processing by an ion milling device. For example, a product named "Arblade (registered trademark) 5000" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The cross-section of the sample is observed by a SEM (Scanning Electron Microscope). For example, a product named "SU8030" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. For each of the 10 composite particles, the thickness of the target portion (coating layer, first layer, second layer) is measured in 20 fields of view. The arithmetic average of the thicknesses of the 200 points in total is regarded as the thickness of the target portion.
[0040] The thickness of each layer may be measured in an element mapping image by SEM-EDX (Energy Dispersive X-ray Spectrometry). In the element mapping image, an element representative of each part is selected. As an example, Ni may be selected as the representative element of the core particle (active material), F as the representative element of the first layer (fluoride SE), and S as the representative element of the second layer (sulfide SE).
[0041] The "coverage rate" is measured by the following procedure. A cross-sectional sample of the composite particle is prepared in the same manner as the sample for measuring the thickness of the coating layer. In the cross-sectional SEM image, the length (L0) of the contour line of the core particle (active material) is measured. The length (L1) of the portion of the contour line of the core particle that is covered with at least one of the fluoride SE and the sulfide SE is measured. The coverage rate is the percentage of L1 divided by L0. The coverage rate is measured for each of 20 composite particles. The arithmetic average of the 20 coverage rates is considered to be the "coverage rate."
[0042] For example, L0 and L1 may be calculated by performing image processing on an element mapping image obtained by SEM-EDX.
[0043] A "hollow particle" refers to a particle in which the area of the cavity in the center is 30% or more of the cross-sectional area of the entire particle in a cross-sectional image of the particle (e.g., a cross-sectional SEM image, etc.). A "solid particle" refers to a particle in which the area of the cavity in the center is less than 30% of the cross-sectional area of the entire particle in a cross-sectional image of the particle.
[0044] "D50" refers to the particle size at which the cumulative frequency of the smaller particle sizes reaches 50% in a volume-based particle size distribution. D50 can be measured using a laser diffraction particle size distribution analyzer.
[0045] The "average Feret diameter" is measured on a two-dimensional image of a particle. The arithmetic mean of the maximum Feret diameters of 20 or more particles is the "average Feret diameter".
[0046] <Electrode material> The electrode material is a raw material of the electrode. The electrode material may be a powder. For example, a paint containing the electrode material may be formed. The paint may be applied to the surface of a current collector to produce an electrode.
[0047] The electrode material includes composite particles. In addition to the composite particles, the electrode material may further include, for example, free components. The free components are present in a state of being free from the composite particles. The free components may be in the form of particles. The free components may include, for example, active materials, fluoride SEs, sulfide SEs, etc. The free components may include, for example, chippings. The free components may include, for example, by-products obtained in the manufacturing process of the composite particles. The free components may include, for example, residues of raw materials for the composite particles. For example, a part of the sulfide SEs input as raw materials for the composite particles may not contribute to the formation of the composite particles and may become free components. The electrode material may be composed of, for example, 0 to 10% free components and the remaining composite particles in terms of mass fraction. The mass fraction of the free components may be, for example, 0 to 5% or 1 to 3%. The maximum Feret diameter of the free components may be, for example, 1 nm to 5 μm.
[0048] 《Composite particles》 FIG. 1 is a first conceptual diagram showing an example of a composite particle in this embodiment. The composite particle 30 includes a core particle 10 and a coating layer 20. The D50 of the composite particle 30 may be, for example, 1 to 30 μm, 2 to 20 μm, 3 to 15 μm, 3 to 6 μm, or 4 to 5 μm. The composite particle 30 may have any shape. The composite particle 30 may be, for example, spherical, ellipsoidal, flaky, fibrous, or the like.
[0049] 《Coating layer》 The coating layer 20 covers at least a part of the surface of the core particle 10. For example, the coating layer 20 may be formed so as to fill in the unevenness of the surface of the core particle 10. The coating layer 20 may cover the entire surface of the core particle 10. The coating layer 20 may cover a part of the surface of the core particle 10. The coating layer 20 may be distributed in an island shape on the surface of the core particle 10. The coverage may be, for example, 50 to 100%, 60 to 100%, 70 to 100%, 80 to 100%, or 90 to 100%. The higher the coverage, the more reduced the initial resistance is expected, for example.
[0050] The thickness of the covering layer 20 may be, for example, 6 to 300 nm, or 11 to 150 nm. As the covering layer 20 is thinner, for example, a reduction in initial resistance is expected.
[0051] The coating layer 20 includes a first layer 21 and a second layer 22. At least a portion of the first layer 21 is disposed between the core particle 10 and the second layer 22. For example, the first layer 21 may directly coat the surface of the core particle 10. For example, the second layer 22 may coat the entire first layer 21. The second layer 22 may coat a portion of the first layer 21. There may be a portion of the first layer 21 exposed from the second layer 22. There may be a portion of the second layer 22 in direct contact with the core particle 10.
[0052] <1st layer, Fluoride SE> The first layer 21 is, so to speak, the "lower layer". The first layer 21 may, for example, entirely cover the core particles 10 without any gaps. The first layer 21 may have a thickness of, for example, 1 to 100 nm or 1 to 50 nm. The thinner the first layer 21 is, for example, the more reduction in the initial resistance is expected.
[0053] The first layer 21 contains a first solid electrolyte (first SE). The first SE is a fluoride. Fluoride SE tends to have a less likely increase in reaction resistance during durability.
[0054] The first SE can have any composition as long as it contains F. The first SE may, for example, contain Li and F. The first SE may be represented by, for example, the following formula (1). Li 6-nx M x F6…(1) In the above formula (1), x satisfies 0 < x < 2. M is at least one selected from the group consisting of a semi-metal atom and a metal atom excluding Li. n indicates the oxidation number of M.
[0055] M may consist of a single atom or may consist of multiple types of atoms. When M consists of multiple types of atoms, n indicates the weighted average of the oxidation numbers of each atom. For example, when M contains Ti (oxidation number = +4) and Al (oxidation number = +3), the molar ratio of Ti to Al is "Ti / Al = 3 / 7", and x = 1, n becomes 3.3 according to the formula "n = 0.3×4 + 0.7×3".
[0056] x may satisfy, for example, 0.1 ≦ x ≦ 1.9, 0.2 ≦ x ≦ 1.8, 0.3 ≦ x ≦ 1.7, 0.4 ≦ x ≦ 1.6, 0.5 ≦ x ≦ 1.5, 0.6 ≦ x ≦ 1.4, 0.7 ≦ x ≦ 1.3, 0.8 ≦ x ≦ 1.2, or 0.9 ≦ x ≦ 1.1.
[0057] M may, for example, contain an atom with an oxidation number of +4. M may, for example, contain an atom with an oxidation number of +3. M may, for example, contain an atom with an oxidation number of +4 and an atom with an oxidation number of +3.
[0058] M may, for example, include at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr. M may, for example, include at least one selected from the group consisting of Al, Y, and Ti. M may, for example, include at least one selected from the group consisting of Al and Ti.
[0059] The first SE may be expressed, for example, by the following formula (2). Li 3-x Ti x Al 1-x F6…(2) In the above formula (2), x may satisfy, for example, 0≦x≦1, 0.1≦x≦0.9, 0.2≦x≦0.8, 0.3≦x≦0.7, or 0.4≦x≦0.6.
[0060] The first SE may be, for example, particulate. That is, the first layer 21 may be, for example, a particulate layer. The particulate layer is an aggregate of particles. The average Feret's diameter of the first SE may be, for example, 0.1 to 1 times the thickness of the first layer 21.
[0061] <2nd layer, sulfide SE> The second layer 22 is, so to speak, an "upper layer." The second layer 22 may form the outermost layer of the composite particle 30. The second layer 22 may surround the core particle 10 without any gaps. The second layer 22 may be thicker than the first layer 21, for example. The second layer 22 may have a thickness of, for example, 5 to 200 nm, or 10 to 100 nm.
[0062] The second layer 22 includes a second solid electrolyte (second SE). The second SE is a sulfide. The sulfide SE can exhibit high ionic conductivity. The second SE can have any composition as long as it contains S (sulfur). The second SE may include, for example, Li, P, and S. The second SE may further include, for example, O, Ge, Si, etc. The second SE may further include, for example, a halogen, etc. The second SE may further include, for example, I, Br, etc. The second SE may be, for example, a glass ceramic type or an argyrodite type. The second SE is, for example, LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-GeS2-P2S5, Li2S-P2S5, Li4P2S6, Li7P3S 11 and Li3PS4.
[0063] For example, "LiI-LiBr-Li3PS4" refers to a sulfide SE produced by mixing LiI, LiBr, and Li3PS4 in any molar ratio. For example, the second SE may be produced by a mechanochemical method. "Li2S-P2S5" includes Li3PS4. Li3PS4 can be produced, for example, by mixing Li2S and P2S5 in "Li2S / P2S5=75 / 25 (molar ratio)".
[0064] The second SE may be, for example, particulate. That is, the second layer 22 may be, for example, a particle layer. The average Feret diameter of the second SE may be equal to or less than the thickness of the second layer 22. The average Feret diameter of the second SE may be equal to or less than 1 / 3 (one third) of the maximum Feret diameter of the core particle 10. When the size of the second SE is sufficiently small compared to the size of the core particle 10, the coating layer 20 tends to easily fill in the unevenness of the surface of the core particle 10. This is expected to improve, for example, the coverage rate. The average Feret diameter of the second SE may be, for example, 5 to 200 nm, or 10 to 100 nm.
[0065] <Additional ingredients in the second layer> FIG. 2 is a second conceptual diagram showing an example of a composite particle in this embodiment. The second layer 22 may further include first flakes 41 in addition to the second SEs. The first flakes 41 include the first SEs. That is, the second layer 22 may further include the first SEs. However, in the second layer 22, the volume fraction of the second SEs is larger than the volume fraction of the first SEs. The first flakes 41 may be dispersed in the second layer 22. The first flakes 41 may be generated, for example, when the first SEs fall off from the first layer 21. The first flakes 41 may be generated, for example, when some of the first SEs do not contribute to the formation of the first layer 21.
[0066] The second layer 22 may further include second flakes 42 in addition to the second SE. The second flakes 42 include an active material. That is, the second layer 22 may further include an active material. However, in the second layer 22, the volume fraction of the second SE is larger than the volume fraction of the active material. The second flakes 42 may be dispersed in the second layer 22. The second flakes 42 may be generated by, for example, loss of the core particles 10.
[0067] The second layer 22 may further include third flakes 43 in addition to the second SE. The third flakes 43 include the first SE and an active material. That is, the second layer 22 may further include both the first SE and the active material. In the second layer 22, the first SE may be attached to the active material. For example, the third flakes 43 may be generated by the loss of a part of the first layer 21 together with a part of the core particle 10 during the formation of the second layer 22.
[0068] Here, the first flakes 41, the second flakes 42, and the third flakes 43 are collectively referred to as "flakes". The flakes may have any shape. The flakes may be, for example, spherical, ellipsoidal, flaky, or fibrous. The flakes have a maximum Feret diameter of, for example, 1 nm or more. The flakes have a maximum Feret diameter equal to or less than the thickness of the second layer 22. One composite particle 30 may contain, for example, 1 to 100 pieces, 20 to 80 pieces, 30 to 70 pieces, or 30 to 50 pieces of flakes. The number of flakes is measured in 10 or more composite particles 30. In a cross-sectional SEM image of the composite particle 30, the flakes having a maximum Feret diameter of 1 nm or more are counted. The arithmetic average in the 10 composite particles 30 is adopted.
[0069] FIG. 3 shows an example of a cross-sectional SEM image of a composite particle and an element mapping image by SEM-EDX. The element mapping image of S shows the distribution of the second layer (second SE). The element mapping image of F shows the distribution of the first layer (first SE). The element mapping image of Ni shows the distribution of the core particles (active material). For example, it can be seen from the element mapping image of S and the element mapping image of Ni that the second layer contains chippings of active material. The composite particle in FIG. 3 is composed of 4.6% first SE, 10% second SE, and the remaining active material in volume fraction. For example, the area fraction in the cross-sectional SEM image or element mapping image can be regarded as the volume fraction.
[0070] The second layer may be composed of, for example, 0-10% of the first flakes, 0-10% of the second flakes, 0-10% of the third flakes, and the remainder of the second SE, in terms of volume fraction. The second layer may be composed of, for example, 1-5% of the first flakes, 1-5% of the second flakes, 1-5% of the third flakes, and the remainder of the second SE, in terms of volume fraction. The second layer may be composed of, for example, 1-3% of the first flakes, 1-3% of the second flakes, 1-3% of the third flakes, and the remainder of the second SE, in terms of volume fraction.
[0071] <Blend amount> The amounts of the active material, the first SE, and the second SE are arbitrary. For example, the first SE may be 1 to 10 parts by mass, or 2 to 3 parts by mass, relative to 100 parts by mass of the active material. For example, the first SE may be 1.3 to 8.8 parts by mass, 2.4 to 4.8 parts by mass, or 3.8 to 4.8 parts by mass, relative to 100 parts by mass of the active material.
[0072] The amount of the second SE may be less than the amount of the first SE. The amount of the second SE may be more than the amount of the first SE. The mass ratio of the first SE to the second SE (first SE / second SE) may be, for example, 0.5 to 2. For example, the amount of the second SE may be 0.1 to 20 parts by mass or 0.5 to 15 parts by mass per 100 parts by mass of the active material.
[0073] The total amount of the first SE and the second SE mixed per 100 parts by mass of the active material may be, for example, 2.7 to 11.5 parts by mass, 4 to 7.5 parts by mass, 5.1 to 7.5 parts by mass, or 6.5 to 7.5 parts by mass.
[0074] Core Particle The core particle 10 is a base material of the composite particle 30. The composite particle 30 may contain one core particle 10 alone. The composite particle 30 may contain a plurality of core particles 10. The core particle 10 may be, for example, a secondary particle. The secondary particle is an aggregate of primary particles. For example, chipping may occur along grain boundaries of the primary particles. The D50 of the secondary particles may be, for example, 1 to 30 μm, 2 to 20 μm, 3 to 15 μm, 3 to 6 μm, or 4 to 5 μm. The average Feret's diameter of the primary particles may be, for example, 0.01 to 3 μm.
[0075] The core particle 10 may have any shape. The core particle 10 may be, for example, spherical, ellipsoidal, flake-like, fibrous, etc. The core particle 10 may be a solid particle or a hollow particle.
[0076] The core particle 10 includes an active material. The active material can cause an electrode reaction. The core particle 10 may include, for example, a positive electrode active material. The positive electrode active material may include any component. The positive electrode active material may include, for example, at least one selected from the group consisting of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(NiCoMn)O2, Li(NiCoAl)O2, Li(NiCoMnAl)O2, and LiFePO4. For example, "(NiCoMn)" in "Li(NiCoMn)O2" indicates that the sum of the composition ratios in parentheses is 1. As long as the sum is 1, the amount of each component is arbitrary. Li(NiCoMn)O2 is, for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.4 Co 0.3 Mn 0.3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.5 Co 0.3 Mn 0.2 O2, LiNi 0.5 Co 0.4 Mn 0.1 O2, LiNi 0.5 Co 0.1 Mn 0.4 O2, LiNi 0.6 Co 0.2 Mn 0.2 O 2、 LiNi 0.6 Co 0.3 Mn 0.1 O 2、 LiNi 0.6 Co 0.1 Mn 0.3 O 2、 LiNi 0.7 Co 0.1 Mn 0.2 O 2、 LiNi 0.7 Co 0.2 Mn 0.1 O 2、 LiNi 0.8 Co 0.1 Mn 0.1 O 2、 and LiNi 0.9 Co 0.05 Mn0.05 It may contain at least one selected from the group consisting of O2. Li(NiCoAl)O2 is, for example, LiNi 0.8 Co 0.15 Al 0.05 O2 or the like may be included.
[0077] The positive electrode active material may be represented by, for example, the following formula (3). Li 1-y Ni x M 1-x O2…(3) 0.5 ≦ x ≦ 1 -0.5 ≦ y ≦ 0.5 In the above formula (3), M may contain, for example, at least one selected from the group consisting of Co, Mn, and Al. x may be, for example, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more.
[0078] The positive electrode active material may contain, for example, an additive. The additive may be, for example, a substitutional solid solution atom or an interstitial solid solution atom. The additive may be an adherent adhering to the surface of the positive electrode active material (primary particle). The adherent may be, for example, a simple substance, an oxide, a carbide, a nitride, a halide, or the like. The addition amount may be, for example, 0.01 to 0.1, 0.02 to 0.08, or 0.04 to 0.06. The addition amount indicates the ratio of the amount of the additive to the amount of the positive electrode active material. The additive may contain, for example, at least one selected from the group consisting of B, C, N, halogen, Sc, Ti, V, Cu, Zn, Ga, Ge, Se, Sr, Y, Zr, Nb, Mo, In, Sn, W, and lanthanoids.
[0079] The core particle 10 may contain, for example, a negative electrode active material. The negative electrode active material may contain any component. The negative electrode active material is, for example, natural graphite, artificial graphite, soft carbon, hard carbon, Si, SiO x (0 < x < 2), Si-based alloy, Sn, SnO x (0 < x < 2), Li, Li-based alloy, and Li4Ti5O 12It may contain at least one selected from the group consisting of. SiO x (0 < x < 2) may be doped with, for example, Mg or the like. A composite material may be formed by supporting an alloy-based active material (for example, Si or the like) on a carbon-based active material (for example, graphite or the like).
[0080] <Method for manufacturing composite particles> FIG. 4 is a schematic flowchart of the method for manufacturing composite particles in this embodiment. The method for manufacturing composite particles in this embodiment (hereinafter may be abbreviated as "this manufacturing method") includes "(a) preparation of core particles" and "(b) formation of a coating layer".
[0081] 《(a) Preparation of core particles》 This manufacturing method includes preparing core particles 10. The core particles 10 can be prepared by any method. For example, the core particles 10 may be synthesized. For example, off-the-shelf core particles 10 may be obtained.
[0082] 《(b) Formation of a coating layer》 This manufacturing method includes forming a coating layer 20. The coating layer 20 is formed so as to cover at least a part of the surface of the core particles 10. The coating layer 20 includes a first layer 21 and a second layer 22. For example, the first layer 21 and the second layer 22 may be sequentially formed by a mechanochemical method. For example, the first layer 21 can be formed by mixing the core particles 10 and the first SE under conditions where a mechanical load is applied. When forming each layer, for example, the number of chips (the amount of chipping generated) included in the second layer 22 can be adjusted according to the magnitude of the mechanical load applied to the core particles 10 or the like. The magnitude of the mechanical load can be adjusted, for example, by the type of device, the operating conditions of the device, etc. The mechanical load includes, for example, shear load, impact load, compression load, etc. For example, in a dry particle compounding device (for example, a circulation type mechanofusion device), a relatively large shear load and impact load can occur. For example, in a dry stirring granulator, a wet kneading device (for example, a blade rotation type kneading device, a container rotation type kneading device, a kneader, etc.), a relatively small shear load can occur.
[0083] <All-solid-state battery> FIG. 5 is a conceptual diagram of the all-solid-state battery in this embodiment. The all-solid-state battery 200 includes a power generating element 150. The all-solid-state battery 200 may include, for example, an exterior body (not shown). The exterior body may house the power generating element 150. The exterior body may have any shape. The exterior body may be, for example, a pouch made of a metal foil laminate film, or a case made of metal.
[0084] The all-solid-state battery 200 may include a single power generating element 150, or may include a plurality of power generating elements 150. The plurality of power generating elements 150 may form, for example, a series circuit or a parallel circuit.
[0085] The power generating element 150 includes a positive electrode 110, a separator layer 130, and a negative electrode 120. That is, the all-solid-state battery 200 includes electrodes. At least one of the positive electrode 110 and the negative electrode 120 includes the electrode material in this embodiment. That is, the electrode includes the electrode material.
[0086] 《Positive electrode》 The positive electrode 110 is layered. The positive electrode 110 may include, for example, a positive electrode active material layer and a positive electrode current collector. For example, the positive electrode active material layer may be formed by applying a positive electrode mixture to the surface of the positive electrode current collector. The positive electrode current collector may include, for example, aluminum foil or the like. The positive electrode current collector may have a thickness of, for example, 5 to 50 μm.
[0087] The positive electrode active material layer may have a thickness of, for example, 10 to 200 μm. The positive electrode active material layer is in close contact with the separator layer 130. The positive electrode active material layer includes a positive electrode mixture. The positive electrode mixture includes a positive electrode active material and a sulfide SE. The positive electrode mixture may include the electrode material in this embodiment. The positive electrode mixture may further include a fluoride SE, a conductive material, a binder, and the like. Details of the electrode material, the positive electrode active material, the fluoride SE, and the sulfide SE are as described above.
[0088] The sulfide SE can form an ion conduction path in the positive electrode active material layer. The amount of the sulfide SE may be, for example, 1 to 200 parts by volume, 50 to 150 parts by volume, or 50 to 100 parts by volume, relative to 100 parts by volume of the positive electrode active material. The sulfide SE mixed in the positive electrode mixture (positive electrode active material layer) may be the same type as the second SE contained in the electrode material, or may be a different type.
[0089] The conductive material can form an electronic conduction path in the positive electrode active material layer. The amount of the conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the positive electrode active material. The conductive material may contain any component. The conductive material may contain, for example, at least one selected from the group consisting of carbon black (CB), vapor grown carbon fiber (VGCF), carbon nanotube (CNT) and graphene flake (GF). The CB may contain, for example, at least one selected from the group consisting of acetylene black (AB), Ketjen Black (registered trademark) and furnace black.
[0090] The binder can bind the solid materials together. The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the positive electrode active material. The binder may contain any component. The binder may contain, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), styrene butadiene rubber (SBR), butadiene rubber (BR), and polytetrafluoroethylene (PTFE).
[0091] 《Negative electrode》 The negative electrode 120 is layered. The negative electrode 120 may include, for example, a negative electrode active material layer and a negative electrode current collector. For example, the negative electrode active material layer may be formed by applying a negative electrode mixture to the surface of the negative electrode current collector. The negative electrode current collector may include, for example, copper foil, nickel foil, or the like. The negative electrode current collector may have a thickness of, for example, 5 to 50 μm.
[0092] The negative electrode active material layer may have a thickness of, for example, 10 to 200 μm. The negative electrode active material layer is in close contact with the separator layer 130. The negative electrode active material layer includes a negative electrode mixture. The negative electrode mixture includes a negative electrode active material and a sulfide SE. The negative electrode mixture may include the electrode material in this embodiment. The negative electrode mixture may further include a fluoride SE, a conductive material, a binder, and the like. Details of each material are as described above. The sulfide SE, the conductive material, and the binder may be the same or different between the positive electrode 110 and the negative electrode 120.
[0093] <Separator layer> The separator layer 130 may have a thickness of, for example, 1 to 100 μm. The separator layer 130 may also be referred to as an "SE layer." The separator layer 130 is interposed between the positive electrode 110 and the negative electrode 120. The separator layer 130 separates the positive electrode 110 from the negative electrode 120. The separator layer 130 includes a sulfide SE. The separator layer 130 may further include a fluoride SE and a binder. Details of each material are as described above. The sulfide SE may be the same or different between the separator layer 130 and the positive electrode 110. The sulfide SE may be the same or different between the separator layer 130 and the negative electrode 120. EXAMPLES
[0094] <Experiment 1> As described below, electrode materials, positive electrodes, and all-solid-state batteries according to Nos. 1-1 to 1-4 were manufactured.
[0095] No.1-1 Li(NiCoAl)O2 was prepared as the core particles. Hereinafter, "Li(NiCoAl)O2" may be abbreviated as "NCA."
[0096] A precursor solution was prepared by mixing ethoxylithium, pentaethoxyniobium, and ultra-dehydrated ethanol. The surface of NCA was coated with the precursor solution to form composite particles. The composite particles were heat-treated to convert the precursor solution into a coating layer. The coating layer consisted of a first layer. The first layer contained an oxide SE. The oxide SE had a composition of LiNbO3.
[0097] No.1-2 Fluoride SE was synthesized by mixing LiF, TiF4, and AlF3 in a planetary ball mill. 2.7 Ti 0.3 Al 0.7 The composition of the compound was F6. 2.7 Ti 0.3 Al 0.7 "F6" may be abbreviated as "LTAF."
[0098] A "Nobilta NOB-MINI (manufactured by Hosokawa Micron Corporation)" was prepared as a particle compositing device. In the particle compositing device, 48.7 parts by mass of NCA and 1.3 parts by mass of LTAF were subjected to a compositing process to form composite particles. The operating conditions of the device were as follows:
[0099] Power: 12W per gram of material Rotational speed: 6000 rpm Processing time: 30 minutes
[0100] The composite particle included a coating layer. The coating layer consisted of a first layer. The first layer included LTAF.
[0101] No.1-3 Li2S-P2S5 was prepared as the sulfide SE. The sulfide SE was a glass ceramic. Hereinafter, "Li2S-P2S5" may be abbreviated as "LPS".
[0102] The composite particles according to No. 1-1 were prepared. In a particle composite device, 71.6 parts by mass of the composite particles and 3.4 parts by mass of LPS were subjected to composite processing. The operating conditions of the device were as follows.
[0103] Power: 3W per gram of material Rotational speed: 1000 rpm Processing time: 30 minutes
[0104] The composite process resulted in the formation of a coating layer including a first layer and a second layer. The first layer contained LiNbO3. The second layer contained LPS.
[0105] No.1-4 The composite particles according to No. 1-2 were prepared. In a particle composite device, 71.6 parts by mass of the composite particles and 3.4 parts by mass of LPS were subjected to composite processing. The operating conditions of the device are as follows.
[0106] Power: 3W per gram of material Rotational speed: 1000 rpm Processing time: 30 minutes
[0107] The composite treatment resulted in the formation of a coating layer comprising a first layer and a second layer. The first layer contained LTAF. The second layer contained LPS.
[0108] <Evaluation> A positive electrode containing the composite particles (electrode material) obtained above was manufactured. Furthermore, a test battery (all-solid-state battery) containing the positive electrode was manufactured. The configuration of the test battery is as follows.
[0109] Exterior: Aluminum laminated film Composition of the positive electrode active material layer: Composite particles + LPS + AB + VGCF + binder Positive electrode collector: Aluminum foil Negative electrode active material: Li4Ti5O 12
[0110] 《Initial resistance》 The SOC (State Of Charge) of the test battery was adjusted to 50%. The test battery was discharged for 2 seconds at an hourly rate of 60.2C. The initial resistance was calculated from the voltage drop and current during discharge. The initial resistance in Table 1 below is a relative value to the initial resistance of No. 1-1. The initial resistance of No. 1-1 is considered to be 100%.
[0111] Note that "C" is the symbol for the current rate. At a rate of 1C, the rated capacity of the battery is discharged in 1 hour.
[0112] Resistance Increase Rate After the initial resistance was measured, a durability test was carried out, that is, a pulse charge-discharge cycle was carried out under the following conditions:
[0113] Test temperature: 80℃ SOC range: 50~60% Charge / discharge cycle count: 800
[0114] After the durability test, the post-durability resistance was measured in the same manner as the initial resistance. The resistance increase rate was calculated by dividing the post-durability resistance by the initial resistance. The resistance increase rates in Table 1 below are relative values to the resistance increase rate of No. 1-1. The resistance increase rate of No. 1-1 is considered to be 100%.
[0115] Electronic Conductivity A positive electrode with the same specifications as the positive electrode used in the test battery was prepared. Two disk samples were punched out from the positive electrode by punching. The area of each disk sample was 1 cm. 2 The two disk samples were pressed together so that the positive electrode active material layers faced each other to form a laminate. The thickness and DC resistance of the laminate were measured. The electronic conductivity was calculated from the thickness and DC resistance. The electronic conductivity in Table 1 below is a relative value to the electronic conductivity of No. 1-2. The electronic conductivity of No. 1-2 is considered to be 1.00.
[0116] [Table 1]
[0117] As shown in Table 1 above, the resistance increase rate of No. 1-4 was significantly reduced compared to the other samples. The coating layer of No. 1-4 includes a first layer and a second layer. The first layer includes a fluoride SE (LTAF). The second layer includes a sulfide SE (LPS).
[0118] In Table 1, the electronic conductivity tends to improve when the second layer is coated with LPS. This is presumably because the core particles (active material) or the pieces of the first layer remain in the second layer, preventing the pieces from diffusing into the electrode.
[0119] <Experiment 2> As described below, electrode materials, positive electrodes, and all-solid-state batteries according to Nos. 2-1 to 2-6 were manufactured.
[0120] No.2-1, 2-5 No.2-1 has the same specifications as No.1-2. No.2-5 has the same specifications as No.1-4.
[0121] No.2-2~2-4, 2-6 As shown in Table 1 below, electrode materials, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1-4, except that the amount of LPS was changed.
[0122] <Evaluation> The resistance increase rate was measured in the same manner as in Experiment 1. The resistance increase rates in Table 2 below are relative values to the resistance increase rate of No. 1-1. The resistance increase rate of No. 1-1 is considered to be 100%.
[0123] The electronic conductivity was measured in the same manner as in Experiment 1. The electronic conductivity in Table 2 below is a relative value to No. 2-1 (No. 1-2). The electronic conductivity of No. 2-1 is considered to be 1.00.
[0124] [Table 2]
[0125] As shown in Table 2 above, for example, by adjusting the blending amount of the second SE (LPS), it is expected that the resistance increase rate will be further reduced.
[0126] In Table 2 above, there is a tendency that the electronic conductivity improves as the blending amount of the second SE (LPS) increases. [Explanation of symbols]
[0127] 10 core particle, 20 coating layer, 21 first layer, 22 second layer, 30 composite particle, 41 first flake, 42 second flake, 43 third flake, 110 positive electrode, 120 negative electrode, 130 separator layer, 150 power generating element, 200 all-solid-state battery.
Claims
1. Composite particles included, The composite particle includes a core particle and a coating layer, the coating layer covers at least a part of the surface of the core particle, The core particle includes an active material, The coating layer includes a first layer and a second layer, At least a portion of the first layer is disposed between the core particle and the second layer, the first layer includes a first solid electrolyte; the second layer includes a second solid electrolyte; the first solid electrolyte is a fluoride; The second solid electrolyte is a sulfide, For 100 parts by mass of the active material, The first solid electrolyte is 2 to 3 parts by mass, and The second solid electrolyte is 1.3 to 4.8 parts by mass. electrode material.
2. The second layer further includes the first solid electrolyte in addition to the second solid electrolyte, In the second layer, a volume fraction of the second solid electrolyte is larger than a volume fraction of the first solid electrolyte. The electrode material according to claim 1 .
3. the second layer further contains the active material in addition to the second solid electrolyte, In the second layer, a volume fraction of the second solid electrolyte is larger than a volume fraction of the active material. The electrode material according to claim 1 .
4. the second layer further contains, in addition to the second solid electrolyte, the first solid electrolyte and the active material; In the second layer, a volume fraction of the second solid electrolyte is larger than a total volume fraction of the first solid electrolyte and the active material. The electrode material according to claim 1 .
5. In the second layer, the first solid electrolyte is attached to the active material. The electrode material according to claim 4.
6. The first solid electrolyte has the formula (1): <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> 6-nx <h2 style=";text-align:left;direction:ltr"> 8<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> F<h2 style=";text-align:left;direction:ltr"> 6 <h2 style=";text-align:left;direction:ltr"> …(1) is represented by In the formula (1), x satisfies 0<x<2, M is at least one selected from the group consisting of metalloid atoms and metal atoms other than Li; n indicates the oxidation number of M; The electrode material according to any one of claims 1 to 5.
7. In the formula (1), M contains an atom having an oxidation number of +4; The electrode material according to claim 6.
8. In the formula (1), M contains an atom having an oxidation number of +3; The electrode material according to claim 6.
9. In the formula (1), M includes at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr; The electrode material according to claim 6.
10. The electrode material according to claim 1 , electrode.
11. Comprising the electrode of claim 10 All solid state battery.
Citation Information
Patent Citations
Composite active material and manufacturing method thereof
JP2014154407A
Positive electrode material, and battery
WO2021187391A1
